The images of Ottoman Turkey in the selected Malay periodicals in the early twentieth century - Mansor Majdin, Mohamad Firdaus; Zakariya, Hafiz (Asian Scholars Network, 2024)
This paper analyses the Malay reformist writers’ interest and admiration of the Ottoman in several Malay newspapers. Such coverages were specially providedby al-Imam, Lengkongan Bulan, and Neracha. These newspapers were published in two major Malayan port cities, Penang and Singapore in the early 20th century and edited by some prominent Malay reformist writers. This study investigates why the Malay reformists paid considerable attention and coverage to the Ottoman. These Malay reformists were branded as Kaum Muda (Young Faction) who favoured reforms and renewal in society in comparison to Kaum Tua (Old Faction) who favoured a conservative approach. Using historical-content-textual analyses, this study demonstrates that frequent coverages of the Ottoman is derived from the Malay reformists’ interest in the progress and advancement of the Ottoman as well as the latter’s interest in the Pan-Islamism project championed by the Ottoman Sultan, Sultan Abdul Hamid I.